Prospective analysis of endoscopic measurement of pyloric impedance planimetry and its association with clinical outcomes of gastric peroral endoscopic myotomy - Farooq, Aimen; Bani Fawwaz, BahaAldeen; Zhang, YiYang; Hasan, Muhammad K.; Mian, Arooj; Khan, Hafiz; Brar, Tony S.; Singh, Sanmeet; Viana, Artur; Hayat, Maham; Xiao, Yasi; Aljohani, Waleed; Abbasi, Abdullah; Chandan, Saurabh; Pathak, Sagar; Kadkhodayan, Kambiz; Arain, Mustafa A.; Cosgrove, Natalie; Jain, Deepanshu; Inayat, Irteza; Yang, Dennis (Endoscopy, 2025)
The functional luminal imaging probe (FLIP) assesses pyloric sphincter physiology. We prospectively used FLIP to evaluate the association between pyloric measurements and clinical outcomes of gastric peroral endoscopic myotomy (G-POEM) in patients with refractory gastroparesis.This was a single-center prospective trial of patients who underwent G-POEM between January 2022 and March 2024. FLIP was performed before G-POEM, immediately after G-POEM, and at follow-up (median 6 months). Clinical response was defined as an improvement of ≥1 point on the Gastroparesis Cardinal Symptom Index (GCSI). A receiver operating characteristic curve was constructed to evaluate the relationship between FLIP measurements and response to G-POEM.Clinical response was achieved in 64/90 patients (71.1%) at a median of 6 months. Mean (SD) FLIP distensibility index (DI) before G-POEM was significantly lower among responders vs. non-responders (7.10 [2.75] vs. 9.24 [3.14] mm2/mmHg; P = 0.002). Mean DI increased significantly in both groups immediately after G-POEM, but this remained elevated only among responders (10.4 [4.4] mm2/mmHg; P < 0.001), returning toward baseline among non-responders (9.7 [4.7] mm2/mmHg; P = 0.69) at 6 months’ follow-up. A DI threshold of 7.35 mm2/mmHg before G-POEM had an area under the curve of 0.72 and yielded a specificity of 80.8% and sensitivity of 60.6%.Sustained improvement in pyloric FLIP measurements was seen in patients with a clinical response to G-POEM. Patients who responded to G-POEM had a lower baseline DI compared with non-responders. Additional studies optimizing and standardizing FLIP protocols in patients undergoing G-POEM are needed.